262 AN UNUSUAL CAUSE OF PACEMAKER MALFUNCTION WITH NON-COMMON ELECTROCARDIOGRAPHIC PRESENTATION AND UNEXPECTED ECHOCARDIOGRAPHIC FINDING. (15th December 2022) - Franchina, Antonio Gabriele; Minardi, Alessandro; Marini, Claudia; Calì, Floriana; Fiorista, Lorenzo; Pala, Massimo; Cereda, Alberto; Lucreziotti, Stefano
Abstract: This clinical case shows the diagnostic challenge and the management of a 79 y-o male with arterial hypertension, tabagism, obesity and a recent hospitalization for infero-lateral STEMI undergoing primary PCI of Right Coronary Artery with 2 DES and following DDDR MRI PM (pacemaker) implantation (through left cephalic vein) due to the development of persistent 2:1 AV block (atrio-ventricular block). One month later, admission at Emergency Department for syncope. The admission therapy included Aspirin plus Clopidogrel, Ramipril, Atorvastatin. Normal parameters were found at laboratory analyses. The electro-stimulator activity evaluation showed a PM malfunction with ventricular capture failure . Thus, the increase of PM output up to electric ventricular capture (8 Volt/120 msec) was performed, but the following Electrocardiogram (ECG) showed a PM-induced rhythm with RBBB-morphology . Then, the bedside Echocardiogram showed an apparent presence of a linear hyper-echogenic image (lead?) into left ventricle with no inter-ventricular septal defect neither inter-ventricular shunt, inter-atrial septal hypermobility with no evident inter-atrial shunt at rest; while a chest Radiography identified the atrial and ventricular leads with no accurate individuation of their position. The patient was admitted in Intensive Cardiac Care Unit with confirmation of intermittent failure to ventricular capture and RBBB-morphology during PM-induced rhythm at telemetry monitoring . Due to Electrocardiographic and (above all) Echocardiographic findings, a strong suspect of abnormal position of the ventricular lead into left ventricle through a possible PFO has been raised. A chest Computed Tomography was performed confirming the anomalous position of the ventricular lead: the atrial lead was in the right atrium whereas the ventricular lead reached the left atrium through an inter-atrial defect/patent foramen ovale (PFO), then crossing the mitral valve up to left ventricle . The PM-lead repositioning was scheduled two days after. With intra-operative fluoroscopy, a further verify of leads position was observed (the ventricular one into left ventricle through PFO and mitral valve, the atrial one mildly displaced upwards) and the leads repositioning was performed. After positioning of temporary stimulator lead in right ventricle, the ventricular lead has been withdrawn from left-side chambers and positioned into septal-apical right ventricle ; furthermore, the position of right atrial lead has been optimized (because of frequent spontaneous passage to the left atrium through the PFO, during manual maneuvers). Finally, the optimal stability of the device was obtained, as well as the optimal atrial and ventricular capture during stimulation test. During the observation in Cardiology Unit in following days, the telemetry monitoring and ECG showed a PM-induced rhythm, without capture nor sensing failure . The chest Radiography confirmed the correct position of atrial and ventricular leads. Finally, the pre-discharge transthoracic Echocardiography showed a LVEF 57% with no valvular pathology nor pericardial effusion, and with atrial and ventricular leads into right-side chambers.